Competencies of physical education and school sports coordinators in managing sports event in libmanan districts, division of camarines sur - Aguja, Leo Gascon (San Miguel, Iriga City: University of Saint Anthony, 2015)
Competencies of physical education and school sports coordinators in managing sports event in libmanan districts, division of camarines sur
Includes bibliographical references.
English